Voltage mode control of coupled inductor bidirectional DC to DC converter - Narasimharaju, B L; Dubey, S P; Singh, S P (2010 IEEE International Conference of Electron Devices and Solid-State Circuits, 2010)
In this paper, authors propose a coupled inductor bidirectional converter, and design of classical PI controllers in voltage mode control. The proposed converter has the high voltage diversity which enables battery module of low voltage to be interfaced with the high-voltage dc bus or the micro grid for subsequent utilization. The working principles, design guidelines, and PI based voltage controller design of the proposed converter is discussed in detail. Theoretical principles of battery fed converter with voltage controller are validated through simulation in the Matlab/Simulink environment. Also, prototype coupled inductor BDC converter is developed and performances are evaluated.